2019
DOI: 10.1177/1538574419844073
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy of Vascular Trauma—Current Options and Review of the Literature

Abstract: Objective: To review the current use of endovascular techniques in trauma. Summary Background Data: Multiple studies have demonstrated that, despite current guidelines, endovascular therapies are used in instances of arterial trauma. Methods: The existing literature concerning arterial trauma was reviewed. Studies reviewed included case reports, single-center case series, large database studies, official industry publications and instructions for use, and society guidelines. Results: Endovascular therapies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 150 publications
(254 reference statements)
1
15
0
Order By: Relevance
“…3 Despite the lack of guideline-support for a role for endovascular intervention in peripheral vascular trauma, endovascular management of all vascular injuries has become more common. 1,3,7,8 Endovascular intervention is a particularly viable alternative for managing partial transection, pseudoaneurysm, arteriovenous fistula, intimal defects, dissection, and vascular injuries within the thoracic cavity. 7 Additionally, endovascular therapy is appealing in patients with extreme obesity due to avoid incisions and minimize wound complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Despite the lack of guideline-support for a role for endovascular intervention in peripheral vascular trauma, endovascular management of all vascular injuries has become more common. 1,3,7,8 Endovascular intervention is a particularly viable alternative for managing partial transection, pseudoaneurysm, arteriovenous fistula, intimal defects, dissection, and vascular injuries within the thoracic cavity. 7 Additionally, endovascular therapy is appealing in patients with extreme obesity due to avoid incisions and minimize wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…Published experiences continue to remain limited; however, endovascular techniques are a widely accepted and effective alternatives for a highly selective group of patients and injuries. 7 -11 A study of the NTBD found an increase in endovascular procedures from 0.3% in 2002 to 9.0% in 2010, with even greater frequency among blunt trauma patients, 0.4% in 2002 to 13.2% in 2010. 1 Endovascular modalities are more common in patients with upper extremity and intrathoracic cavitary injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern nowadays concerning endovascular therapy in blunt thoracic trauma patients is the lack of long-term results. Possible explanations reside in the considerable loss to follow-up 5,26 and the lack of standardization for surveillance, despite considerations for the patients’ usually young age and the expected life-time cumulative radiation exposure. Given all this, and with studies supporting the fact that most complications occur in the early postoperative period, several surveillance programs are suggested, mainly after thoracic endovascular aortic repair (TEVAR) for blunt thoracic aortic injury.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although open surgery remains the gold-standard, the endovascular approach is becoming increasingly relevant. 5 in an attempt to reduce the morbidity and mortality associated with the open approach. We report a case of IA injury extending to the subclavian artery with a pseudoaneurysm formation successfully treated with covered stenting of IA and its bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Although aortic injury classifications are initially based on thoracic injuries, abdominal injuries can be described with the same classification. Intimal flaps <10mm are safely managed with blood pressure control (B-blockers) and antiplatelet therapy (aspirin) [16,18]. Large intimal flaps, not complicated with thrombosis or arterial insufficiency, are treated with medical management and follow-up CT imaging in 48-72 hours.…”
Section: Abdominal Aortamentioning
confidence: 99%